The Effectiveness of The Integrated Training during" the General and Special Preparation Period " for Developing Some Skills variables for Soccer Players Under 19 Years - SADOUK, hamza; kabouya, Mohammed (sports creativity, 2025)
This study aimed to detection and determine the effectiveness the integrated training during the general and special preparation period for developing some basic football skills by applying a training program and rigorous tests on the research by experts in the field the skills side the" U-S-C" and" U-S -M-A" teams under 19 years old. They activist in the second national section by 16 teams amateurs in eastern of Algeria, who represent the research community. They were chosen in an intentional survey way. After subjecting it to the scientific conditions of measurement before and after measurement after applying the integrated physical and skill training program with the ball, as for the statistical aspect, than the statistical analysis of the results of the research using by IBM SPSS Statistique 20. “ T ” test was used for interconnected and unrelated samples tests. To analyze the graph of the results obtained in terms of results achieved hypotheses resulted after the dimensional measurement between the experimental team "USC "and the control teams "USMA" for development of the basic skills of the following: Test : 1-control the ball in a specific area.2- scrolling with receiving and control test .3- test of correction accuracy on the target